SIKAP PETANI WORTEL TERHADAP KEBERADAAN SUB TERMINAL AGRIBISNIS (STA) WATUSAMBANG DI KECAMATAN TAWANGMANGU, KABUPATEN KARANGANYAR - Annisaa Dwi Prihatin; Eny Lestari; Hanifah Ihsaniyati (Universitas Sebelas Maret, 2018)
This research are to analyze the farmers’s attitude to the existence of the STA Watusambang, analyze the factors forming attitudes, and analyze the relationships between the factors forming attitudes and the farmers’s attitude to the existence of STA Watusambang. The basic method used in this research was descriptive quantitative with survey technique. The location of the research was determined purposively in Blumbang Village, Tawangmangu Subdistrict, Karanganyar Regency. Sampling method used proportional random sampling, there were 60 carrot farmers chosen from each member farmer groups (4 farmer groups). The attitude- forming of carrot farmers in this research is age, formal education, personal experience, culture, and exposure to the mass media. The relationship of attitude- forming factors with the farmers’s attitude could be known by using Rank Spearman analysis. The result of this research indicate that the attitude of carrot farmers against to STA Watusambang 50.0% as much as the farmer respondents have a neutral attitude. The largest percentage age farmer respondents in the age category 37-44 years, formal education and culture in low category, personal experience and influence others who are considered important in the medium category, and exposure to the mass media in the category. Relationship analysis of test results showed there are a very significant relationship (α=0,01) between the influence of others considered important, personal experiences, and culture with an attitude of carrot farmers against STA; There is no significant relationship between age, formal education, and the media with the attitude of carrot farmers against the STA.